Hamka: Character Education's Relevance to Contemporary Islamic Education - Dinata, Syaiful; Aulia Ali Rahman; Veni Sofia (Indonesian Journal of Islamic Educational Review, 2025)
The gap that occurs regarding the issue of adolescent character continues to be a hot topic in this country. One of the figures who is very strong in paying attention to character education in Indonesia is Hamka, for that reason it is necessary to study in depth the concept of character education according to Hamka. This research uses a library study type of research with the main source of Hamka's book. The results of the study show that Hamka calls character with the term personality. While a Great Person is someone who is able to make himself have a great personality character which includes (a) having charm, (b) being smart, (c) considering feelings, (d) being brave, (e) being wise, (f) having good views, (g) knowing himself, (h) maintaining physical health, (i) being wise in speaking, and (j) believing in oneself. Meanwhile, the relevance of Hamka's perspective on character education to contemporary Islamic education now lies in the instillation of valuable values in humans. Hamka states that personality is a collection of traits and strengths, which show a person's superiority over others. In other words, Hamka also explains that personality is a collection of intellectual traits, will, ideals and body shape. This, according to Hamka, is what sets humanity apart from others. Islamic education today remains anchored in the instillation of noble moral values, and this, of course, cannot be valued by anything. Therefore, it can be said that the current Islamic educational process remains rooted in the same principle: morality, but the difference lies in the challenges of an ever-changing era. Thus, contemporary Islamic education faces significant challenges in technological advancement if it fails to instill the character education championed by Hamka.